2017
DOI: 10.1039/c7ta04194b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of iron substitution in lithium rich layered oxides Li2Ru1−xFexO3: triggering the anionic redox reaction

Abstract: The partial substitution of Ru with Fe in Li2RuO3 stabilises the layered structure during cycling, leading to a stable capacity of ∼250 mA h g–1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…11a , the capacity retention of ID-Li 2 RuO 3 is significantly higher than that of R-Li 2 RuO 3 in all cases, even when the initial specific discharge capacity of ID-Li 2 RuO 3 (260 mAh g –1 for 2.0–5.0 V) turns higher than that of R-Li 2 RuO 3 (246 mAh g –1 for 2.0–4.2 V). The relatively low capacity retention of R-Li 2 RuO 3 is consistent with previous literature reports 44 47 . Thus, we conclude that the ID-Li 2 RuO 3 electrode is more stable than the R-Li 2 RuO 3 electrode upon cycling, as predicted above.…”
Section: Resultssupporting
confidence: 91%
“…11a , the capacity retention of ID-Li 2 RuO 3 is significantly higher than that of R-Li 2 RuO 3 in all cases, even when the initial specific discharge capacity of ID-Li 2 RuO 3 (260 mAh g –1 for 2.0–5.0 V) turns higher than that of R-Li 2 RuO 3 (246 mAh g –1 for 2.0–4.2 V). The relatively low capacity retention of R-Li 2 RuO 3 is consistent with previous literature reports 44 47 . Thus, we conclude that the ID-Li 2 RuO 3 electrode is more stable than the R-Li 2 RuO 3 electrode upon cycling, as predicted above.…”
Section: Resultssupporting
confidence: 91%
“…In addition, the plot of the average discharge potential is displayed in Figure d. A high discharge potential, which was above 3.63 V (vs. Li/Li + ) at the first discharge, was maintained at 3.38 V after 100 cycles, indicating a suppressed potential fade. The discharge potential was much higher than other Li‐rich materials owing to Fe substitution …”
Section: Resultsmentioning
confidence: 94%
“…demonstrated that the reversible capacity of Li 1+ x Fe y Mn 1− x − y O 2 is generated from the Fe 3+ /Fe 4+ redox couple at approximately 4 V, which was further confirmed by the 57 Fe Mössbauer spectrum . Tarascon and co‐workers also found that in Li 4 FeSbO 6 and Li 2 Ru 1‐ x Fe x O 3 , Fe 3+ can be oxidized to Fe 4+ , which was accompanied by the oxidation of O 2− to O 2 2− during delithiation. Although most observations verify the oxidation of Fe 3+ , a clear explanation of the redox mechanism for either Fe or O in the Ni‐, Fe‐, and Mn‐containing Li‐rich materials is still lacking.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The details of the redox reaction mechanism in Li-rich x Li 2 MnO 3 •(1-x )LiMO 2 cathode is still ambiguous and under intense discussion, although it is generally accepted that the anionic (O 2 − ) redox processes plays an important role. Combing oxygen K-edge and transition metal l -edges soft XAS and in situ hard XAS, the charge compensation mechanism in this system has been extensively investigated [173][174][175][176][177][178] . Typically reversibly shifts between the charged/discharged states are observed for Ni and Co l -edge XAS spectra, indicating that the Ni and Co ions reversibly participate in the charge compensation.…”
Section: Soft X-ray Xasmentioning
confidence: 99%